Enhancing caregiver resilience: A systematic review of interventions for chronic disease management - Saeedeh Mohammadi Saber; Behzad Rahimian (BioSocial Health Journal)
Introduction: Caregivers of patients with chronic diseases (PwCD) devote a substantial amount of energy to the care of their PwCD. This study aimed to review interventions fostering resilience in caregivers of PwCD. Methods: A systematic review of literature published either through databases Web of Science, PubMed, Scopus, Magiran, and SID or Google Scholar search engine was undertaken. The review was conducted according to the PRISMA review guidelines. Results: Ten studies were included in this review. Quantitative data provides empirical support for the advantages of psychoeducation, mindfulness-based intervention, cognitive behavioral therapy (CBT)-based intervention, and strengthening family coping resources approach, supportive-educational program based on COPE (Coping Orientation to Problems Experienced) model and commitment therapy. Seven out of ten included studies were randomized controlled trials (RCTs). Conclusion: The present review revealed that psychoeducation, mindfulness-based intervention, CBT-based intervention, strengthening family coping resources approach, supportive-educational Program based on COPE model, and commitment therapy may promote resilience amongst the caregivers of PwCD. Although, it remains unclear which specific intervention would be the most efficacious in improving resilience. Additional rigorous clinical trials are necessary to fortify the current limited evidence base for interventions targeting caregiver resilience.